FACTORS OF POLITICAL DECISION MAKING IN THE CONTEXT OF THE EU FRACTIONALIZATION - Головко, В.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This text deals with main factors in the EU political decision making process in the context of its fractionalization. The main role of “center - periphery” relations within the EU and the degree of influence of its particular members in terms of geographical location, economic, political and sociocultural features in this process is underlined.